The Acceptance Model of a National e-Payment in Thailand: Conceptual Framework - Patawee Chaluay; Singha Chaveesuk; Natapon Pantuwong (My University, 2017)
The rapid growth of technology allows people to connect easier also through electronic commerce (e-Commerce).E-Commerce provides a great potential to support the user for trading in products or services with computer networks.Electronic payment (e-Payment) was developed to facilitate e-Commerce transactions.In recent years, the government has been trying to push a national e-Payment system in Thailand to aid economic development.This research will investigate the user's willingness to use a national e-Payment system in Thailand.The proposed model was developed by integrating the unified theory of acceptance and use of technology (UTAUT) with the task technology fit model (TTF) and Initial trust model (ITM).The contribution of this model will be used to examine the acceptance potential of the national e-payment user in Thailand.
Keywords: Conceptual model; Technology Acceptance Model; Technology Adoption and User Behaviour